2001
DOI: 10.4065/76.12.1225
|View full text |Cite
|
Sign up to set email alerts
|

Religious Involvement, Spirituality, and Medicine: Implications for Clinical Practice

Abstract: Surveys suggest that most patients have a spiritual life and regard their spiritual health and physical health as equally important. Furthermore, people may have greater spiritual needs during illness. We reviewed published studies, meta-analyses, systematic reviews, and subject reviews that examined the association between religious involvement and spirituality and physical health, mental health, health-related quality of life, and other health outcomes. We also reviewed articles that provided suggestions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
333
1
41

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(386 citation statements)
references
References 134 publications
(155 reference statements)
11
333
1
41
Order By: Relevance
“…Several studies corroborate the findings of this study (12)(13) . An assessment study with thousands of people regarding the state of happiness and the religious practice evidenced a positive correlation between these variables (12) .…”
Section: Discussionsupporting
confidence: 80%
“…Several studies corroborate the findings of this study (12)(13) . An assessment study with thousands of people regarding the state of happiness and the religious practice evidenced a positive correlation between these variables (12) .…”
Section: Discussionsupporting
confidence: 80%
“…Though dispositional optimism appears to remain stable throughout the adult life span [29], it is important to examine whether this trait is prominent when faced with a life-threatening condition in older age. Finally, spirituality is increasingly considered an important factor in coping with chronic and life threatening illnesses [for reviews, see 30,31] and there is evidence to suggest that it can be as significant as physical health on overall well-being of cancer survivors [32]. We consider these five psychosocial resources to be potentially protective and expect that they will mitigate the psychological impact of cancer diagnosis and treatment and therefore assist in successful long term survivorship.…”
Section: The Stress-coping Modelmentioning
confidence: 99%
“…It is worth noting that the capital did not differ from the inner state in terms of religiosity, which proved to be high in all questions of the instrument used. A meta-analysis 26 has shown that religious involvement and spirituality are associated with better health indices, such as longevity, management skills, and quality of life, and fewer cases of anxiety, depression, and suicide.…”
Section: Discussionmentioning
confidence: 99%